The hemodynamic stability of remimazolam compared with propofol in patients undergoing endoscopic submucosal dissection: A randomized trial - Qiu, Yuwei; Gu, Wei; Zhao, Mingye; Zhang, Yunyun; Wu, Jingxiang (Frontiers in Medicine, 2022)
Objective Hypotension is common in propofol anesthesia. Whether remimazolam could reduce intraoperative hypotension remains unknown. We therefore tested the primary hypothesis that remimazolam reduces the incidence of intraoperative hypotension compared with propofol in adult patients undergoing endoscopic submucosal dissection (ESD) surgery. Materials and methods We conducted a prospective trial to compare patients who received either remimazolam or propofol bolus induction and thereafter intravenous infusion. The hemodynamic parameters were measured using CNAP® Monitor 500 system. Our primary analysis was to compare the incidence of hypotension defined as systolic blood pressure below 90 mmHg between remimazolam and propofol during the whole anesthesia period. Results The incidence of hypotension decreased by 50%, from 67.9% in propofol group to 32.1% in remimazolam group (p < 0.01). Patients received less amount of intraoperative phenylephrine in the remimazolam group than the propofol group (0 [0–40] μg vs. 80 [0–200] μg, p < 0.01). Time-weighted average and cumulative time of hypotension was lower in remimazolam group compared with propofol group (p < 0.05). Cardiac output continuously measured by CNAP was preserved much better in remimazolam group compared with propofol group (p = 0.01), while systemic vascular resistance did not differ between the groups. The median time from discontinuation until full alertness was 4 [3–11.8] min in the remimazolam group compared with 15 [12.0–19.8] min in the propofol group (p < 0.01). Conclusion Remimazolam has better hemodynamic stability than propofol in adult patients undergoing ESD surgery. The benefits of remimazolam on hemodynamic stability and hypotension prevention may be partly contributed to its better preservation of cardiac output. Clinical Trial Registration [http://www.chictr.org.cn/com/25/showproj.aspx?proj=61104], identifier [ChiCTR2000037975].